14 CASE REPORT OF COCAINE-INDUCED PSEUDOVASCULITIS: A COMMONLY OVERLOOKED MIMICKER OF VASCULITIC SYNDROMES. (1st January 2006) - Bhinder, S. K.; Majithia, V.
Abstract : Introduction: Cocaine use can present with a number of rheumatic manifestations. The diagnosis is often missed or delayed, as the history of abuse is denied, there are no specific signs of abuse, and available serological tests cannot establish this diagnosis. We hereby report a patient with cocaine use presenting with a vasculopathic syndrome. Case Report: A 35-year-old AA female with history of CHF due to mitral stenosis and previous DVT presented with a 2-day history of skin rash on both legs. History and review of systems was otherwise unremarkable. She specifically denied use of new medications, recent infections, alcohol or drug abuse. Examination revealed diffuse palpable purpura in a reticular pattern on lower extremities, buttocks, elbows, and forearms, with blisters and desquamation. Systemic examination had no other pertinent findings. Laboratories revealed normal CBC, chemistry, urinalysis, complements, elevated LFTs, ESR of 3, and CRP of 4.7. Detailed work-up including hepatitis panel, HIV, ANA, ANCAs, APL antibodies, lupus anticoagulant, cryoglobulins, multiple blood and urine cultures, and hypercoagulability work-up was negative. Echocardiogram showed no evidence of vegetations. Urine drug screen was positive for cocaine and she admitted to its recent use when confronted. She was treated with prednisone 60 mg/day with improvement in rash and LFTs. The skin biopsy showed fibrin thrombi occluding vessels, extensive hemorrhage, and mild leukocytoclasis. The final report was vasculopathic reaction pattern with cocaine use in differential diagnosis. She was discharged on tapering doses of prednisone and counseled to abstain from cocaine. The final diagnosis was cocaine-associated pseudovasculitis. Discussion and Conclusion: Cases with varied rheumatic manifestations associated with cocaine use have been described including ANCA +ve vasculitis-like syndromes mimicking Wegener's, p-ANCA +ve necrotizing granulomatous vasculitis, HSP with necrotizing vasculitis, Churg-Strauss and urticarial vasculitis. Cases with +ve p- and c-ANCAs but with disparity to anti-MPO or PR3 specificities have been reported. In our patient, all the work-up including ANCAs was negative. A correct diagnosis is essential as some cases treated with steroids and immunosuppressives had a fatal outcome or persistent symptoms, but abstinence from cocaine resolved the symptoms. This case highlights the fact that there are no specific tests to correctly diagnose cocaine-induced vasculitis and only a high clinical suspicion and urine/serum drug screens can be helpful in such presentations.